Association between the triglyceride–glucose index and left ventricular myocardial work indices in patients with coronary artery disease - Meng, Xuyang; Feng, Baoyu; Yang, Chenguang; Li, Yi; Xia, Chenxi; Guo, Ying; Wang, Xiang; Wang, Fang (Frontiers in Endocrinology, 2024)
Background: Triglyceride-glucose (TyG) index, as an effective surrogate marker of insulin resistance, has shown predictive value in the risk of heart failure in patients with coronary artery disease (CAD). This study aims to investigate the correlation between TyG index and myocardial work measurements in CAD, and to explore its role in detecting early subclinical cardiac dysfunction.: This cross-sectional study included 267 patients diagnosed with CAD and excluding left ventricular myocardial dysfunction in Beijing Hospital. Participants were divided into two groups according to the TyG index level, and myocardial work measurements were compared between groups. The correlation was explored between gradually increased TyG index and subclinical myocardial function in CAD patients. Results: We observed that TyG index was significantly correlated with the global waste work (GWW), and the value of GWW increased progressively with the elevation of TyG index. After adjusting for the effects of confounding factors, TyG index was still independently associated with GWW. Conclusion: An elevated TyG index was independently correlated with early subclinical myocardial dysfunction in CAD patients. Our study demonstrated that the strict control of TyG index may be conducive to forestall the progression of clinical heart failure in CAD patients.